PGRMC1/2 promotes luteal vascularization and maintains the primordial follicles of mice. Issue 4 (October 2018) - Peluso, John J; Liu, Xiufang; Uliasz, Tracy; Pru, Cindy A; Kelp, Nicole C; Pru, James K
Abstract : To determine whether conditional depletion of progesterone receptor membrane component (PGRMC) 1 and PGRMC2 affected ovarian follicle development, follicle distribution was assessed in ovaries of young (≈3-month-old) and middle-aged (≈6-month-old) control ( Pgrmc1/2 fl/fl ) and double conditional PGRMC1/2-knockout ( Pgrmc1/2 d/d ) mice. This study revealed that the distribution of primary, preantral and antral follicles was not altered in Pgrmc1/2 d/d mice, regardless of the age. Although the number of primordial follicles was similar at ≈3 months of age, their numbers were reduced by ≈80% in 6-month-old Pgrmc1/2 d/d mice compared to age-matched Pgrmc1/2 fl/fl mice . The Pgrmc1/2 d/d mice were generated using Pgr-cre mice, so ablation of Pgrmc1 and Pgrmc2 in the ovary was restricted to peri-ovulatory follicles and subsequent corpora lutea (CL). In addition, the vascularization of CL was attenuated in Pgrmc1/2 d/d mice, although mRNA levels of vascular endothelial growth factor A ( Vegfa ) were elevated. Moreover, depletion of Pgrmc1 and Pgrmc2 altered the gene expression profile in the non-luteal component of the ovary such that Vegfa expression, a stimulator of primordial follicle growth, was elevated; Kit Ligand expression, another stimulator of primordial follicle growth, was suppressed and anti-Mullerian hormone, an inhibitor of primordial follicle growth, was enhanced compared to Pgrmc1/2 fl/fl mice. These data reveal that luteal cell depletion of Pgrmc1 and 2 alters the expression of growth factors within the non-luteal component of the ovary, which could account for the premature demise of the adult population of primordial follicles. In summary, the survival of adult primordial follicles is dependent in part on progesterone receptor membrane component 1 and 2.